GAMBARAN TINGKAT PENGETAHUAN ORANG TUA TENTANG IMUNISASI MEASLES RUBELLA PADA ANAK - Mutiara Fannisa; Darwin Karim; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Measles rubella immunization is an attempt to decide of transmission of the measles and rubella virus using the measles rubella vaccine. In giving immunization to children, parents hold the most important role and parents knowledge is very influential on the health of their children. The purpose of this research is to describe the level of knowledge by parents to children with measles rubella immunization. The sample of the study were 379 respondents taken by purposive sampling technique that is parents who have children aged 9 months to 15 years who have not received measles rubella immunization with a simple descriptive research design with cross sectional approach. A measuring instrument used is a questionnaire sheet. The results showed that the highest proportion of all respondents were aged 26-35 years (36,4%). Based on the gender of the respondents the majority are women (71,5%), the last majority of the education was high schools/ vocational school (71,5%), more than half of the respondents were housewives/ unemployed (68,9%) and almost all respondent were muslim (95,8%). Based on the age of the children of the respondents, most of them had not received measles rubella immunization at preschool age (34,6). And also, based on the level of knowledge of parents on immunization of measles rubella is at sufficient level (42,5%). It is expected that to parents will be more active in a seeking for information to increase knowledge about measles rubella immunization. Keywords: child, immunization measles rubella, level knowledge, parents.